Aprendizagem baseada em projetos na investigação dos serviços ecossistêmico dos manguezais em Estância-SE - Ramos, Camila Silva (2022)
Mangroves are essential to the existence of life and constitute environments that have several Ecosystem Services (ESS). The school, in turn, acts as a potential space for the construction of socio-environmental knowledge and the formation of ecological subjects capable of defending the existence of the ecosystem and the people who depend on mangroves. To this end, it is essential to think about active teaching and learning processes. The central problem of this research revolves around the socio-environmental problems about the SEs offered by the mangroves in the municipality of Estância, Sergipe, and the lack of a critical Environmental Education work of the school with the community, in favor of the conservation of the SEs of the mangroves. The objective of this research is to analyze the development of the active Project Based Learning (PBA) methodology for the conservation of mangrove SEs, at the Diocesan Institute of Estância, located in the municipality of Estância. The hypothetical-deductive approach was used to develop the dissertation. The research procedures were developed from the steps: recognition of the research area; presentation of the project proposal to the team of managers and teachers of the school; presentation, discussion and execution of the steps of the active methodology of ABP, with the students; and the construction of the e-book about the use of ABP in Environmental Sciences. The data collection technique used was systematic observation. The data were collected through the theoretical and practical activities performed in each step of ABP. The data were organized, systematized and categorized based on Bardin's content analysis (1977). The BPA execution plan occurred from ten meetings: presentation of the project to the students; conceptualization of ecosystem services and socio-environmental impacts; presentation of the activity; expeditionary learning; debate about the artifacts and presentation of artifacts proposals by groups; documentary "No rio, no mar"; new debate about the artifacts; construction and finalization of artifacts; publication of projects and artifacts; feedback of the publications with the students of the Diocesan Institute of Estancia that resulted in the expansion of the critical eye. The results revealed the identification of the SEs offered by the mangroves of the southern coast of Sergipe, as well as the main anthropogenic tensors and socio-environmental impacts that affect the locality's mangroves. The research fostered the protagonism for the formation of ecopolitical subjects for the conservation of the mangrove SEs in the search for the transformation of their reality with the production of artifacts. Finally, the elaboration of an e-book so that other schools, teachers and managers have access to the production and can reflect on critical Environmental Education with the use of active methodologies. In concluding the research, it was possible to understand the need for a continuous process of critical environmental education practices for the formation of ecopolitical subjects and the importance of the learning process using active methodologies.